2003
DOI: 10.1128/jvi.77.14.7964-7977.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Viral σ1 Protein and Glycoconjugates Containing α2-3-Linked Sialic Acid Are Involved in Type 1 Reovirus Adherence to M Cell Apical Surfaces

Abstract: Reovirus is a nonenveloped, 85-nm icosahedral pathogen that enters the mouse intestinal Peyer's patch mucosa by adhering to M cells and then exploiting the antigen-transporting activity of these specialized epithelial cells (2,50,73). When introduced into the intestinal lumens of adult mice, reovirus type 1 Lang (T1L) adheres to the apical surfaces of M cells but generally not to those of enterocytes, which cover the vast majority of the mucosa. It is known that T1L infection of the mouse mucosa in vivo requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 72 publications
4
94
0
Order By: Relevance
“…The T3D C change at nucleotide 77 confers a valine-to-alanine change at position 22 in the 1 tail and a glutamine-to-histidine change at position 3 in 1s, whereas nucleotide 1234 confers a threonine-to-alanine change at position 408 in the 1 head. These residues are not associated with any known antibody epitope, receptor-binding site, or protease-sensitive region (7,8,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Interestingly, our F virions were treated with HAT protease for 2 h at the concentrations shown.…”
Section: Discussionmentioning
confidence: 99%
“…The T3D C change at nucleotide 77 confers a valine-to-alanine change at position 22 in the 1 tail and a glutamine-to-histidine change at position 3 in 1s, whereas nucleotide 1234 confers a threonine-to-alanine change at position 408 in the 1 head. These residues are not associated with any known antibody epitope, receptor-binding site, or protease-sensitive region (7,8,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Interestingly, our F virions were treated with HAT protease for 2 h at the concentrations shown.…”
Section: Discussionmentioning
confidence: 99%
“…Many colorectal tumors retain the capacity to form a mucus layer 22,23 and this may interfere with the infection of tumor cells by oncolytic viruses like reovirus T3D. 24 Interestingly, s1 from reovirus T3D possesses a latent glycosyl hydrolase activity that is uncovered during the generation of ISVPs. It has been suggested that ISVPs utilize this activity to hydrolyze (part of) the glycosidic portion of the mucus layer to allow infection of otherwise resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…After washing, the membrane was incubated for 1 h with swine anti-rabbit-RPO (Dako) (1:5000). The signals were visualized using an enhanced chemiluminescence system (Roche) 24 h after labeling and cell extracts or tumor fragments were prepared in sample buffer and were analyzed with electrophoresis on long 45 cm sodium dodecyl sulfatepolyacrylamide gel. Gels were dried and exposed to radiographic film.…”
Section: Western Blottingmentioning
confidence: 99%
“…Such pathogens include EHEC and EPEC strains of Escherichia coli (Fitzhenry et al, 2002;Phillips et al, 2000), as well as Shigella flexneri and Salmonella typhymurium (Jensen et al, 1998). Viruses may also use M cells as a point of entry and specific receptors for HIV (Fotopoulos et al, 2002) and reovirus (Helander et al, 2003) on M cells have been identified.…”
Section: Cellsmentioning
confidence: 99%